2020
DOI: 10.1038/s41467-020-18690-4
|View full text |Cite
|
Sign up to set email alerts
|

Polyunsaturated fatty acids and p38-MAPK link metabolic reprogramming to cytoprotective gene expression during dietary restriction

Abstract: The metabolic state of an organism instructs gene expression modalities, leading to changes in complex life history traits, such as longevity. Dietary restriction (DR), which positively affects health and life span across species, leads to metabolic reprogramming that enhances utilisation of fatty acids for energy generation. One direct consequence of this metabolic shift is the upregulation of cytoprotective (CyTP) genes categorized in the Gene Ontology (GO) term of “Xenobiotic Detoxification Program” (XDP). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 73 publications
1
26
0
Order By: Relevance
“…It is therefore likely that increased levels of oxidation as observed in isp-1;ctb-1 mutant worms lead to the NSY-1/ASK1 activation, which subsequently drives p38 MAPK signalling cascade. In further agreement with our findings, SEK-1 induces a cytoprotective machinery in dietary restriction-mediated longevity, by increasing the nematode's xenobiotic detoxification program [ 84 ], while both SEK-1 and SEK-3 were identified in a screen for factors regulating extended the lifespan of C. elegans mitochondrial mutants [ 85 ]. In the later study, PMK-3 was shown to be a key regulator of longevity in isp-1(qm150) and nuo-6(qm200) mutant worms, and upon nuo-2 and cco-1 RNAi, although no further mechanistic insight was provided [ 85 ].…”
Section: Discussionsupporting
confidence: 86%
“…It is therefore likely that increased levels of oxidation as observed in isp-1;ctb-1 mutant worms lead to the NSY-1/ASK1 activation, which subsequently drives p38 MAPK signalling cascade. In further agreement with our findings, SEK-1 induces a cytoprotective machinery in dietary restriction-mediated longevity, by increasing the nematode's xenobiotic detoxification program [ 84 ], while both SEK-1 and SEK-3 were identified in a screen for factors regulating extended the lifespan of C. elegans mitochondrial mutants [ 85 ]. In the later study, PMK-3 was shown to be a key regulator of longevity in isp-1(qm150) and nuo-6(qm200) mutant worms, and upon nuo-2 and cco-1 RNAi, although no further mechanistic insight was provided [ 85 ].…”
Section: Discussionsupporting
confidence: 86%
“…Together, the altered gene expression profile of starved planarians implies that silencing of cct3A is associated with an enhanced sensitivity towards p38 MAPK signaling, autophagy and potentially apoptosis, as expected from the depletion of PI(18:1/18:1). It is tempting to speculate that consequent p38 MAPK activation links dietary restriction to cytoprotective gene expression 79 .…”
Section: Resultsmentioning
confidence: 99%
“… 81 In terms of types of fatty acids, the elevated abundance of the mono- and poly-unsaturated fatty acids in response to CR is a key component of cell membrane structures and has been revealed to upregulate pro-survival mechanisms such as cellular detoxification. 82 Taken together, these results indicate that reinforced rates of both fatty acid synthesis and breakdown are vital controllers of CR-mediated longevity. In addition, special attention should be given when assessing the influence of CR on fatty acid metabolism.…”
Section: Nutrient-associated Molecular Mechanismsmentioning
confidence: 85%